Study of the Vibration Characteristics of Rotating Shafts using Experimental and Finite Element Techniques - Hassan, Luay M.; Ali; Jaafar Khalaf (Basrah Journal for Engineering Sciences, 2023)
The rotor unbalances and misalignment in rotary machines are two major sources of vibration. rotor unbalance and misalignment is omnipresent in all rotating machinery widely used in many industrial applications, posing a serious threat to machine life and operation. The present work is an attempt to investigate the vibration characteristics (Amplitude, FFT, and time waveform) of a rotating mechanical system, which has an unbalanced rotor and misalignment. Vibration signals are acquired using an accelerometer mounted on the bearing housing nearer to the rotor. The FFT analysis of the acquired data revealed the response of an unbalanced rotor under operating conditions. Numerical analysis of the system using ANSYS portrayed the modal frequencies and mode shapes. Transient Structural analysis illustrates the response of the system to different mass unbalances. The results revealed that the magnitude of vibration characteristics significantly increases with excitation frequency and exciting force.